Fluoroalkylether compounds affect microbial community structures and abundance of nitrogen cycle-related genes in soil-microbe-plant systems - Tao Jiang (Elsevier, 2021)
As alternatives to conventional PFAS, ether-PFAS have not been studied much. Their effects to microbial communities, in particular, have not been reported. In this study, we investigated change of microbial community in soil-plant systems dosed with undecafluoro-2-methyl-3-oxahexanoic acid (GenX), dodecafluoro-3H-4,8-dioxanonanoate (ADONA), or 9-chlorohexadecafluoro-3-oxanonane-1-sulfonate (F-53B). It is revealed that the community structure and the species diversity were significantly affected by each of the three ether-PFAS at the two tested concentrations. The only exception was GenX at the low concentration. With respect to nitrification, amoA genes in ammonia oxidizing bacteria were not significantly affected while amoA gene abundance in ammonia oxidizing archaea was significantly decreased. In terms of denitrification, ether-PFAS at different concentrations had different impacts to the three studied genes: nirS, nirK, and norZ. This study thus demonstrated that ether-PFAS could bring significant changes to the soil microbial community structure and functions.